STYLISTIC-PRAGMATIC OF A FIGURATIVE LANGUAGE AND SPEECH ACTS IN QUEEN’S SONGS ON A NIGHT AT THE OPERA’S ALBUM - Haris Diar Rizki; Merry Lapasau (INFERENCE: Journal of English Language Teaching, 2021)
Abstract: The research was conducted to analyze stylistic pragmatic of figurative language and speech acts in Queen's songs on A Night at The Opera. The method of study is descriptive analysis. The result shows that: 1) there are six kinds of figurative language Metaphor 14 times, hyperbole 40 times, personification 19 times, simile three times, metonymy once, and synecdoche. The most dominant type of figurative language is hyperbole, which occurs 40 times. 2) 3 types of speech acts occur in this song: 12 songs, which are those 20 lines of lyrics are considered imperatives. However, there are only a few lyrics using interrogative and the rest using exclamative. 3) There are four occurrences of illocutionary acts found in the song. They are representatives, directives, commisive, and verdictives. Representative is dominant—perlocutionary acts with 14 times of occurrences. Directive occurs three times. Verdictive occurs in a relatively small number, two occurrences. The lowest type of illocutionary act is commisive as it occurs only once. Keywords: pragmatic; figurative language; speech acts; song analysis